RETIREMENT, PENSIONS AND DEPRESSION AMONG OLDER ADULTS IN CHINA, ENGLAND, MEXICO, AND THE U.S. (11th November 2018) - Shelley, M; Lu, P
Abstract: Previous studies have shown positive effects of retirement on older adults' health with age-associated variation. Socioeconomic status is associated with older adults' health, but few studies have discussed the effect of pension types. This study explores the effects of retirement, and of public and private pensions, on older adults' mental health by comparing differences between countries and age-groups. Harmonized data were analyzed from the international family of Health and Retirement surveys in 2012–2013 in China, England, Mexico, and the US (n=97, 978). Respondents were asked if they were retired and received public and/or private pensions. Mental health was measured by the Center for Epidemiologic Studies Depression Scale. Full Information Maximum Likelihood and bootstrap methods were used to address non-normal data with missing values. Results showed that retirement significantly predicted depression for younger age-groups; the positive effect decreased with age in the US and England but increased in Mexico and China. Effects of public pensions were insignificant for China, but significantly negative for England, positive for the US, and robustly positive for Mexico. Effects of private pensions were significantly positive and stronger than for public pensions except in Mexico. Our findings suggest that continuity theory of normal aging has cross-cultural applicability. The Life-Course, Ecological Model of Retirement Transition works for developed countries, but reversely for developing countries. Cross-national differences in effects of pensions may be attributed to the subsistence function of public pensions and the flexibility of private pensions. Providing larger public pensions and more private pension choices are recommended.